Removal of Solids from Palm Oil Mill Effluent and Paint Wastewater Using Electrocoagulation Technique - Joseph Tagbo Nwabanne; Ozioma Onyinye Oguegbu; Chinedu Matthew Agu (International Journal of Electrochemistry)
Electrocoagulation has been employed as a treatment technique for treating various wastewaters. This study focuses on the performance of electrocoagulation process for the treatment of Palm Oil Mill Effluent (POME) and Paint Wastewater (PW) using iron electrodes. POME obtained from local palm oil producers and PW from a paint industry, both in Enugu state of Nigeria, were treated by electrocoagulation using two iron electrodes. Effects of current density, electrocoagulation time, pH, and temperature were studied. Results revealed that this process could reduce the concentration of Total Suspended and Dissolved Solids (TSDP), in both POME and PW. The highest removal efficiencies of 65% and 76% were obtained for POME and PW, respectively, at 3 Amps, 60min, pH of 10, and 50°C for POME and 3 Amps, 60min, pH of 6, and 60°C for PW. Of the two kinetic models studied, second-order kinetic model fitted best to the obtained experimental kinetic data. From this study, it can be concluded that electrocoagulation is effective in the treatment of POME and PW.